Edukasi Pemenuhan Gizi Mikro dan Makro Terhadap Tumbuh Kembang Anak Desa Powelua - Utami Islamiati; Israh; Putri Afriyani (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2024)
Optimal nutrition supports children's growth and development. However, economic factors, family conditions, productivity, and knowledge about child nutrition are often barriers to achieving good nutrition. Powelua is a village in Banawa Tengah sub-district, Donggala, Central Sulawesi, Indonesia which is an outermost and underdeveloped village. Low education, poor access, and meager income are the objectives for carrying out this activity considering that these are the main reasons why someone does not get a decent and healthy life perfectly. The method of implementing the service is a lecture using visual media in the form of posters. The results of this activity. The results of community service show that knowledge about fulfilling nutrition for children does not have good knowledge, but after the counseling has an impact where knowledge about fulfilling nutrition for children and preparing healthy food menus in households is getting better. From the survey results, the satisfaction score was 88.25%, meaning that there is an update on knowledge, which can be in the form of education on balanced nutrition for children, types of food to help children's growth and development.